Malam Sanjungan Budi for Dato' Sri Mohd Hilmey Mohd Taib - Siti Sarah, Mohamad Rajimi (2018)
Kuantan, 19 Februari – Universiti Malaysia Pahang (UMP) organized Malam Sanjungan Budi, a celebration dedicated to appreciate the contributions of former Chairman of UMP Board of Directors, Dato’ Sri Mohd Hilmey Mohd Taib and its two former members, Dato’ Ahmad Azmey Abu Talib as well as Dato’ Ir. Jamaludin Osman.